Kill Bill. Volume 1 [videorecording (DVD)] - Tarantino, Quentin; Thurman, Uma; Liu, Lucy, 1968-; Fox, Vivica A., 1964-; Chiba, Sonny, 1939-2021- (Miramax Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2004)
Four years after taking a bullet in the head at her own wedding, the bride emerges from a coma and decides its time for payback ... with a vengeance. Having been gunned down by her former boss and his deadly squad of international assassins, it's a kill-or-be-killed fight. She didn't start this deadly series of events, but she is definitely determined to finish the business.